El Derecho a la doble instancia en los fallos de desahucio por traspaso de dominio - Myrian Isabel, Concha Ganán (2021)
ABSTRACT A renter's opposition to eviction due to the transfer of ownership is established in the article 48 at the present Tenancy Law. The last paragraph states: "The resolution will cause execution." The resolution is decisive, without any possibility to appeal for a court order. The right to appeal the court order or resolution in all the procedures, in which rights are decided, is enshrined in the Ecuadorian Republic Constitution, article 76, paragraph 7, literal m. It is also recognized by international Human Rights instruments which are ratified by Ecuador such as American Convention on Human Rights. This investigation entitled "The Right to double instance in eviction judgments due to transfer of the domain", arises from the impossibility of appealing eviction decisions due to transfer of domain. In fact, it intends to determine whether the right to double instance guarantees the eviction decisions due to transfer of ownership. Also, if the right limitation to a double instance violates the normative guarantees and constitutional rights related to due process, defense, an effective judicial protection and legal security. To achieve the proposed objective, a legal, doctrinal, jurisprudential and critical study of the right to double instance has been carried out; and the termination of the lease by the transfer of ownership. Keywords: double instance, eviction, transfer of ownership, appeal, violation of rights, regulatory guarantees. Reviewed and corrected by: Jacqueline Guadalupe Armijos Monar English Professor c.c.0201712858